2011
DOI: 10.1063/1.3525993
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast relaxation and absorption saturation at near exciton resonance in a thin ZnO epilayer

Abstract: We observed ultrafast free exciton thermalization time of 700–900 fs and obtained the magnitude of maximal differential absorption to be 1.8×104 cm−1 with the pumping fluence of 10 μJ/cm2 by measuring transient differential transmission in a thin ZnO epitaxial layer at room temperature. The largest induced transparency occurs near exciton resonance associated with absorption saturation by comparing the excitation from the above band-gap to band-tail states. The pumping dependent transient absorption reveals tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Similar values (1.2 ps, 0.81 ps and 0.69 ps) have been reported earlier [14] for the unspecified photogenerated carrier density. The most recent time-resolved pump-probe optical measurements with the given photogenerated carrier density report slightly shorter relaxation times at higher densities: 0.77 ps [15] and 0.85 ps-0.7 ps [13] (Fig.3, open square and triangle). Other optical time-resolved measurements yielded the following relaxation times: 1ps [7], [8], 0.98 ps [9], 0.86 ps [10], 1 ps [11], 0.8 ps [12], 1.75ps and 0.2 ps [3], <3.5ps [24], <4.5ps [25] and <30fs [6].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar values (1.2 ps, 0.81 ps and 0.69 ps) have been reported earlier [14] for the unspecified photogenerated carrier density. The most recent time-resolved pump-probe optical measurements with the given photogenerated carrier density report slightly shorter relaxation times at higher densities: 0.77 ps [15] and 0.85 ps-0.7 ps [13] (Fig.3, open square and triangle). Other optical time-resolved measurements yielded the following relaxation times: 1ps [7], [8], 0.98 ps [9], 0.86 ps [10], 1 ps [11], 0.8 ps [12], 1.75ps and 0.2 ps [3], <3.5ps [24], <4.5ps [25] and <30fs [6].…”
Section: Discussionmentioning
confidence: 87%
“…Solid lines in Fig. 2 illustrate the semi-empiric Open symbols illustrate the most recent optical measurements: circles [16], square [15] and triangles [13].…”
Section: Hot-electron Fluctuation Measurementsmentioning
confidence: 99%
“…We suppose that the excess hot-electron temperature T e -T b approximately equals the excess noise temperature T n -T b (Figure 7). [22], bullets -worldwide results measured by photoexcitation techniques [8][9][10][11][12][13][14][15][16][17][18][19][20]. Dotted curve is semi-empirical dependence [36].…”
Section: Experimental Datamentioning
confidence: 99%
“…9 Nevertheless, to manufacture ultrafast semiconductor devices, it is crucial to investigate ultrafast carrier dynamics through time-resolved measurement (TRM). The transient carrier behaviors of c-ZnO through the excitation of ultrashort fs lasers have been widely explored in various structures, such as quantum dots, 10 nanowires, 11 multiple quantum wells, 12 thin films, 13 single crystals, 14 etc. For instance, Ou et al reported the thickness related ultrafast carrier dynamics of c-ZnO epifilm through the degenerate pump-probe technique using far-above-bandgap excitation.…”
mentioning
confidence: 99%
“…In addition, the TRM has also been adopted to discuss the electron and hole dynamics from a 97 nm non-polar a-ZnO epifilm through two orthogonal pump polarization (E pu ) configurations, i.e., perpendicular (E pu ⊥c) and parallel (E pu c) electric fields relative to the c-axis. 16 Owing to the large binding energy of ZnO compared with other semiconductor materials, RT transient excitonic dynamics 13 are crucial for developing stabilized luminant devices, but the exciton dynamics have seldom been studied. In a previous report, 16 the main work focused on the ultrafast carrier dynamics of a 97 nm non-polar a-ZnO epifilm above and near the bandedge.…”
mentioning
confidence: 99%